Disease screening and prevention for transgender and gender-diverse adults. Issue 10 (October 2017) - Schmidt, Elizabeth; Rizzolo, Denise
Abstract : ABSTRACT: Primary care clinicians have an important role in the health and wellness of transgender and gender-diverse (TGD) adults and need to know best practices of health maintenance and disease prevention interventions. This article focuses on how exogenous use of sex steroids provided as hormone therapy and gender-affirming procedures affect screening and prevention. Hormone therapy can affect the heart, liver, lipids, bones, brain, skin, and reproductive organs; likewise, behaviors and gender-affirming procedures may alter the risks, prevalence, and screening techniques of sexually transmitted infections. Where applicable, modifications accounting for those differences should be incorporated into the primary care of TGD adults.